Beech versus spruce deadwood as forest microhabitat: does it make any difference to bryophytes?. (4th March 2019) - Goia, Irina; Gafta, Dan
Abstract: The presence data of 153 bryophyte species, recorded on beech (BDW) and spruce (SDW) deadwood in the managed forests within a montane watershed, were analysed by controlling for different plot size, substrate pH and elevation. Only three pleurocarpous species, which were probably remnant epiphytes from live wood, showed relative specificity for BDW, but none to SDW. The few species displaying preference for BDW or SDW were generally true epixylic, mosses and hepatics, respectively. The chances of occurrence of epiphytic (early successional) and epixylic (mid-late successional) taxa on either deadwood species increased and respectively, decreased with the substrate pH. There was no consistent relationship between bryophyte preference to BDW/SDW and elevation. Neither total nor threatened species richness was related to deadwood species identity. However, at 100 cm 2 resolution and within certain extension range, the cumulative number of bryophyte species was significantly higher on BDW than on SDW, despite no significant difference in species pool size. Threatened species richness increased monotonically towards lower elevations, suggesting that valley bottoms might act as refugia with high air humidity. The number of threatened species and in particular, the presence of Lophozia ascendens, were good predictors of total bryophyte richness regardless of deadwood species identity.